Development of Multistage Reactor Mobile Plant for Pyrolysis Oil Production from HDPE Plastic - Md Tahir, Muhammad Hanif (Progress in Engineering Application and Technology, 2022)
Pyrolysis has been rapidly studied in the past decade as its potential of converting such organic waste into biofuels. The overall energy consumption, as well as the quality of the product yield, are affected by the heating rate and the operating temperature. For that purpose, the project is basically divided into three main phases. The first phase is the establishment of the Basic Flow Diagram (BFD) and Process Flow Diagram (PFD). The second stage is the development of schematic drawing, fabrication and commissioning. Finally, the third stage is an analysis of the pyrolysis of oil production from HDPE plastic. The portable multistage pyrolysis reactor of black oil will be able to fabricate and function properly based on the design and analysis involves. Besides, the relationship between temperature and product yield ranges from 150°C to 300°C. The temperature is used as a result of the multistage reactor process. Using two different types of reactors: pyrolysis reactors and nickel reactors. Furthermore, the use of nitrogen N₂ pressure to purge the pressure in the reactor is one of the reasons for the low temperature in this process. According to the analysis of the obtained results, the multistage reactor time required to produce an oil product is 1 hour 30 minutes in parallel with the temperature circulation ranging from 150°C to 300°C. This is due to open area on the surface of the reactor when the temperature exceeds 350°C and will cause leakage on the reactor will affect the temperature and pressure drop. The outcome of this work has the potential to successfully developed a portable test rig bench that complies with the actual plant operating condition.